(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Metabolic dysfunction-associated steatohepatitis (MASH) is a severe, progressive liver disease characterized by hepatic steatosis, inflammation, and fibrosis, which can ultimately lead to cirrhosis or liver failure. For decades, clinical management was strictly limited to lifestyle modifications, with no FDA-approved pharmacological interventions available. This review highlights a historic milestone in hepatology: the 2024 approval of Resmetirom, a first-in-class, liver-directed thyroid hormone receptor-beta (THR-β) agonist. By selectively activating THR-β in hepatocytes, Resmetirom significantly increases hepatic fat metabolism and reduces lipotoxicity without the systemic side effects associated with broader thyroid receptor activation. Clinical data demonstrates its dual efficacy in both resolving MASH and reversing liver fibrosis. This poster explores the biochemical pathophysiology of MASH, the targeted mechanism of action of Resmetirom, and how this breakthrough paves the way for a new era of metabolic pharmacotherapy.